Grasping the concept of value: Exploring students’ economic and financial literacy in citizenship education - Mattias Björklund; Malin Tväråna; Ann-Sofie Jägerskog; Max Strandberg (Journal of Social Science Education, 2022)
Purpose: To explore student’s understandings of financial literacy and economics issues with an aim to inform future teaching designs.